Caring to Care: Applying Noddings' Philosophy to Medical Education. (December 2016) - Balmer, Dorene F.; Hirsh, David A.; Monie, Daphne; Weil, Henry; Richards, Boyd F.
Abstract : The authors argue that Nel Noddings' philosophy, "an ethic of caring, " may illuminate how students learn to be caring physicians from their experience of being in a caring, reciprocal relationship with teaching faculty. In her philosophy, Noddings acknowledges two important contextual continuities: duration and space, which the authors speculate exist within longitudinal integrated clerkships. In this Perspective, the authors highlight core features of Noddings' philosophy and explore its applicability to medical education. They apply Noddings' philosophy to a subset of data from a previously published longitudinal case study to explore its "goodness of fit" with the experience of eight students in the 2012 cohort of the Columbia-Bassett longitudinal integrated clerkship. In line with Noddings' philosophy, the authors' supplementary analysis suggests that students (1) recognized caring when they talked about "being known" by teaching faculty who "cared for" and "trusted" them; (2) responded to caring by demonstrating enthusiasm, action, and responsibility toward patients; and (3) acknowledged that duration and space facilitated caring relations with teaching faculty. The authors discuss how Noddings' philosophy provides a useful conceptual framework to apply to medical education design and to future research on caring-oriented clinical training, such as longitudinal integrated clerkships.